Collaborative Governance Analysis in Eradication of Nancotics in the Province of the Special Capital Region of Jakarta - Bogie Setia Perwira Nusa; Bahrullah Akbar; Aris Djaenuri; Sampara Lukman (Budapest International Research and Critics University, 2022)
Collaborative Governance in eradicating drugs in Indonesia is essentially one solution. However, in reality, in the Province of the Special Capital Region of Jakarta, collaboration in the eradication of drugs is still ongoing. This research is based on the concept of collaborative governance theory according to Morse and Stephens (2012: 565-569). The concept of collaborative governance theory includes Assessment, Initiation, Deliberation and Implementation, while the theoretical concept includes strengths, opportunities, weaknesses and threats. The method used in this study is a qualitative research method with construction characteristics built based on natural conditions, more descriptive in nature while the data obtained through the collection of observation data, interviews and documentation. The results of the study indicate that Collaborative Governance in the Eradication of Narcotics between the National Narcotics Agency Intelligence and the Early Awareness Team of the Provincial Government of the Special Capital Region of Jakarta is still not going well, this is indicated by the weak assessment, in contextual understanding of collaboration, identification of collaborative stakeholders. Lack of initiation of sponsorship roles that may become human resources and funding sources for implementing collaboration and gathering stakeholders to develop working groups in the design process for implementing collaborations. The deliberation is still weak in establishing the basic rules for the implementation of collaboration, deliberation and stakeholder dialogue for the implementation of collaboration and collaboration agreements. Lack of implementation of collaboration structure design, monitoring of agreements and commitments, delivery of results and collaboration. The strategic steps that are the main priority of the coordination procedure are the formation of Early Detection Cadres and Network Mapping with a total average score of 2.7. The model produced in this study is the model of the National Narcotics Agency Deputy for Eradication through the establishment of an Early Detection Cadre and Network Mapping in collaboration with the Provincial/Regency/City/Sub-district Early Awareness Team in the Province of the Special Capital Region of Jakarta. Suggestions to develop Collaborative Governance theory in Narcotics, which include Collaborative Governance theory and Strategy Theory.